2021
DOI: 10.24018/ejmed.2021.3.3.860
|View full text |Cite
|
Sign up to set email alerts
|

Dharavi Slums (Mumbai, India): The Petri Dish of COVID-19 Herd Immunity

Abstract: The first and second serosurvey results of COVID-19 antibodies in Dharavi and Cuffe Parade slums (Mumbai, India) were studied. The seroprevalence data of the slums explained the zero novel coronavirus cases reported in the slum dwellers verified first in real on the ground the concept of much needed herd immunity against the pandemic.  First serosurvey data showed that more than half (57%) of the population of Dharavi was infected with the virus. The antibodies were waned off in two month time and diminished t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…To understand herd immunity, a study was conducted to correlate the seroprevalence and the infection rate in the slums, which showed high seropositivity in the slums of Dharavi. [ 20 ] The present study also showed higher seropositivity in urban areas, as in previous serosurveys conducted during August 2020 when there was a partial lockdown across Karnataka. [ 21 ]…”
Section: Discussionsupporting
confidence: 89%
“…To understand herd immunity, a study was conducted to correlate the seroprevalence and the infection rate in the slums, which showed high seropositivity in the slums of Dharavi. [ 20 ] The present study also showed higher seropositivity in urban areas, as in previous serosurveys conducted during August 2020 when there was a partial lockdown across Karnataka. [ 21 ]…”
Section: Discussionsupporting
confidence: 89%
“…The high infection rate in the state of Kerala compared to the other states of India was explained by the newly established "health index theory" [15], [16]. The absence of a second COVID-19 wave in Dharavi slums (Mumbai, India) was [17] due to the development of mass immunity, 75% of residents had antibodies, against the virus. The viability of the SARS-CoV-2 virus and sanitization methods [18], initial attempts at vaccine development [19], and the application of supercomputer in prevention of infection and treatment [20] were reviewed in the articles mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…The high infection rate in the state of Kerala (India) compared to the other states was explained by the newly established "health index theory" [16], [17]. The absence of the second and third COVID-19 waves in Dharavi slums (Mumbai, India) was explained [18] to be due to the mass immunity (75%) developed among the residents against the virus. The stability of the SARS-CoV-2 virus and sanitization methods [19], initial attempts at vaccine development [20], and the use of supercomputer in preventing the virus spread [21] were reviewed in the articles mentioned.…”
Section: Introductionmentioning
confidence: 99%